Life-threatening event during skin-to-skin contact in the delivery room. (29th December 2010) - Schrewe, Brett; Janvier, Annie; Barrington, Keith
Abstract : After an uncomplicated term delivery, a newborn infant experienced a life-threatening even a few minutes after being born. Few such events have been described before, they may be due to suffocation; minor changes in surveillance can probably prevent these potentially devastating events.